221k views
4 votes
Use the power-reducing formulas to rewrite the expression in terms of first powers of the cosines of multiple angles.

Use the power-reducing formulas to rewrite the expression in terms of first powers-example-1

1 Answer

6 votes

This is the same question as 17042785 (the question number in the site URL), with the exception of using the other identity,


\sin^2x=\frac{1-\cos(2x)}2

We have


2\sin^4(2x)=2(\sin^2(2x))^2=2\left(\frac{1-\cos(4x)}2\right)^2=\frac12(1-\cos(4x))^2

Expand the binomial:


2\sin^4(2x)=\frac12(1-2\cos(4x)+\cos^2(4x))

Using the identity in the previous question,


\cos^2x=\frac{1+\cos(2x)}2

we get


\cos^2(4x)=\frac{1+\cos(8x)}2

So,


2\sin^4(2x)=\frac12\left(1-2\cos(4x)+\frac{1+\cos(8x)}2\right)


2\sin^4(2x)=\frac14\left(3-4\cos(4x)+\cos(8x)\right)

User Moi
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.